USING CHILDREN SHORT STORIES TO ENHANCE STUDENTS' READING COMPREHENSION - Handayani, Merli Puji (2013)
The study informs on the use of children short stories in teaching reading comprehension in one of junior high schools in Bandung. Due to their length, vocabulary, and storyline, children short stories were selected for the purpose to increase students' motivation to read. A classroom action research was conducted in this study in form of three cycles of treatment. The data were collected through various sources: observation sheet, reading test, questionnaire, and interview. The data then were analyzed through triangulation method and reported in qualitative descriptive analysis. The findings revealed despite some limitations, the use of children short stories helped the students to improve their reading comprehension. The result of reading test showed a slightly improvement on the students' average score from 61.09 in diagnostic test increased to 76.28 in Cycle 3 therapeutic test. The result of observation implied that the employment of reading strategies and the characteristic of children short stories gave influences to the improvement of students' reading comprehension. In addition, the results from questionnaire and interview indicated that students were aware of having progress in terms of vocabulary and comprehending the text generally. It is thus recommended for further study to minimize the challenge found in this study and to vary kinds of children short stories used. Key words: a model of teaching, children short stories, reading comprehension, EFL students Penelitian ini menginformasikan tentang penggunaan cerita pendek anak-anak dalam pengajaran reading comprehension di salah satu SMP negeri di Bandung. Dikarenakan tidak terlalu panjangnya cerita, kosakata, dan alur cerita yang menarik, cerita pendek anak-anak dipilih dengan tujuan untuk meningkatkan motivasi siswa dalam membaca. Penelitian tindakan kelas dengan tiga siklus dilaksanakan dalam penelitian ini. Data penelitian dikumpulkan melalui berbagai sumber: observasi, tes, kuesioner, dan wawancara. Data tersebut dianalis melalui metode triangulasi dan dilaporkan secara kualitatif deskriptif. Hasil penelitian disamping berbagai limitasi, menunjukkan penggunaan cerita pendek anak-anak meningkatkan pemahaman siswa dalam membaca. Hasil tes menunjukkan peningkatan nilai rata-rata siswa dari 61.09 pada diagnostik tes meningkat jadi 76.28 pada terapeutik tes diakhir siklus 3. Hasil observasi mengindikasikan penggunaan beberapa strategi membaca dan karakteristik dari cerita pendek anak-anak membantu dalam meningkatkan kemampuan siswa dalam memahami teks. Hasil kuesioner dan wawancara menunjukkan bahwa siswa merasakan kosakata B. Inggris mereka bertambah dan kemampuan memahami suatu teks juga menjadi lebih baik. Oleh karena itu, penelitian selanjutnya agar meminimalisir kekurangan-kekurangan yang ditemukan di penelitian ini dan menambah jenis cerita pendek anak-anak yang akan digunakan. Kata kunci: model pengajaran, cerita pendek anak-anak, reading comprehension, siswa EFL (English for Foreign Language)